ALE-Based Finite Element Simulation of Large Deformation in Bending and Flattening Tests. (2015) - Nie, D.F.; Chen, X.D.; Fan, Z.C.; Wu, Q.G.
Abstract: Steel plates and pipes, widely used in industries, are generally required to examine their plasticity according to bending and flattening tests. To clearly understand large deformation behaviors in bending and flattening tests, finite element models were created to simulate the evolution of bending and flattening by using Abaqus software, and experiments were carried out to verify the simulated results. It was found that classical Lagrangian method tracking material particles was difficult to cope with large deformation due to severe distortion of elements, while the arbitrary Lagrangian-Eulerian (ALE) method combining the advantages of Lagrangian and Eulerian methods was very attractive for solving such issues. The simulated results based on ALE method were dependent on mesh size and contact parameters to some extent, with decreasing the mesh size the portion of yielded elements increased and the spring-back decreased, and the friction could effectively constrain the relative slide of contact pairs and reduce the separation of former from plates. The simulations showed acceptable agreement with the bending and flattening test results. However, some available criteria in current standards, without concern for neutral plane shifting, ignored the separation of former from plates and hence gave values lower than the actual strain, which might lead to incorrect assessment. This study is helpful to modify some improper criteria in standards for bending and flattening tests.